Locking of symmetry breaking and topological phase in an interacting fermionic wire - Dan-Bo Zhang; Zhen Zheng; Y. X. Zhao; Qiang-Hua Wang; Z. D. Wang (Physical Review Research, 2020)
We construct and study an intriguing model of one-dimensional interacting fermion wire, which is enforced to be in a topological phase by the spin-orbit locking structure in the interactions, regardless of the dimerization direction of the Peierls distortion, in sharp contrast to a conventional wisdom. Thorough analyses based upon the bosonization, the renormalization group technique, and the mean-field theory have been made. The novelty of being a pair-hopping fermionic wire lies in that symmetry breaking and the formation of (symmetry-protected) topological configurations are not independent, enriching our understanding of the interplay between topological phase and symmetry breaking. An experimentally feasible scheme is proposed for realizing the model with cold atoms and available techniques.